KAJIAN HUKUM PERLINDUNGAN KONSUMEN TERHADAP KONSUMEN YANG MENGGUNAKAN KARTU KREDIT - Rini T Simangunsong (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
The dynamics of the development of an increasingly modern global society along with the development of its economy has also influenced the pattern of life of the people themselves. Credit cards as an aspect of modern society's life have become a means of payment in lieu of cash which is increasingly in demand by the public or consumers today, because they have their own prestige, and have even become a lifestyle trend in big cities. This is also supported by the many shopping centers that serve cashless payments. In Law Number 8 of 1999 Article 1 paragraph (1) concerning Consumer Protection, it states that